Nuclear Power in the Developing World - Poneman, Daniel (London George Allen & Unwin, 1982)
This book explores the increasingly urgent issue of nuclear power policies in developing countries. The sharp oil price rises of the 1970's attracted widespread attention to nuclear power as an alternative energy source. Meanwhile, more and more developing countries have attained the technological ability to begin nuclear weapon programmes.
Include Bibliography and Index
Keywords: Nuclear industry -- Developing countries